2011
DOI: 10.1152/ajpgi.00245.2011
|View full text |Cite
|
Sign up to set email alerts
|

Secretin is not necessary for exocrine pancreatic development and growth in mice

Abstract: Adaptive exocrine pancreatic growth is mediated primarily by dietary protein and the gastrointestinal hormone cholecystokinin (CCK). Feeding trypsin inhibitors such as camostat (FOY-305) is known to induce CCK release and stimulate pancreatic growth. However, camostat has also been reported to stimulate secretin release and, because secretin often potentiates the action of CCK, it could participate in the growth response. Our aim was to test the role of secretin in pancreatic development and adaptive growth th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Immunofluorescence was performed as described previously [19]. Briefly, pancreatic tissues were fixed for 30 min in 4% formaldehyde (freshly prepared from paraformaldehyde) in PBS, cryoprotected as described [19], embedded in a 1:1 mixture of OCT and 20% sucrose and then 6 μm sections were cut with a CM 1950 Leica Cryostat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence was performed as described previously [19]. Briefly, pancreatic tissues were fixed for 30 min in 4% formaldehyde (freshly prepared from paraformaldehyde) in PBS, cryoprotected as described [19], embedded in a 1:1 mixture of OCT and 20% sucrose and then 6 μm sections were cut with a CM 1950 Leica Cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, pancreatic tissues were fixed for 30 min in 4% formaldehyde (freshly prepared from paraformaldehyde) in PBS, cryoprotected as described [19], embedded in a 1:1 mixture of OCT and 20% sucrose and then 6 μm sections were cut with a CM 1950 Leica Cryostat. The primary polyclonal anti-amylase antibody, and Oregon Green 488 Phalloidin which stains F-actin were diluted 1:1,000, and 1:50, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently the most common technique was dissecting and weighing the pancreas. This yields values for young adults, usually males, fed a control diet, of 8-12 mg pancreatic weight/g body weight for mice (22,64,120,125,143), 22.5 mg PW/gBW for Syrian Hamster (124), 2.5-4 mg PW/g BW for rats (25,34,40,57,123,158), and 0.5-1.1 g PW/kg BW for adult humans (13,127). Note that the relative pancreas size gets smaller as the animal gets larger.…”
Section: Measurement Of Pancreatic Sizementioning
confidence: 99%
“…In both rats and mice the adaptive growth is reversible and when the TI is removed the pancreas returns to its original size (21, 105,106). No dependence on secretin was seen in mice as TI had similar effects in mice where secretin signaling was genetically deleted (120). The evidence as to whether such a feedback loop involving CCK occurs in humans is mixed and may involve proteases other than trypsin (36,72,73).…”
Section: Trypsin Inhibitor Feedingmentioning
confidence: 99%
“…Secretin also increased the content of polyamines in the pancreas which accompanies and is required for growth (28). However, studies in mice with genetically deleted secretin or secretin receptor showed a normal sized pancreas which grew normally in response to elevated endogenous CCK (87). Another proposed action of secretin not fully evaluated is to stimulate the synthesis of pancreatic lipase.…”
Section: Effects Of Secretin On the Pancreas In Vivo Studies Of Secrementioning
confidence: 99%